Karakteristik Biskuit Kelor (Moringa Oliefera) Berbasis Pati Garut (Maranta Arundinacea) dan Tepung Kacang Merah (Phaseolus Vulgaris L.) dengan Variasi Pemanis - Khusnul Khotimah; Dian Rachmawanti Affandi; Rizky Brisha Nuary; Adhitya Pitara Sanjaya; Meli Sulistiowati (Journal of Applied Agriculture, Health, and Technology, 2022)
The majority of biscuits currently assessing their nutritional value in the market are dominated by certain unbalanced compounds. The use of wheat flour and sugar as the main ingredients makes some people with special needs avoid these foods. Biscuits based on arrowroot starch and red bean flour with the addition of Moringa flour extract are expected to complement the nutrition of the biscuits. The substitute sweeteners of palm sugar and sorghum sugar are expected to produce biscuits that are better studied from the chemical, physical and sensory characteristics. This study aims to see the effect of substitution on chemical, physical and sensory characteristics and to determine the best formula by comparing it with control samples. The research design carried out was a completely randomized design with one factor. The sweetener variations used are (granulated sugar: palm sugar) 75:25. 50:50, 25:75, 0: 100 and (granulated sugar: sorghum sugar) 75:25. 50:50, 25:75, 0: 100 and 100% granulated sugar as a control. The results showed that biscuits with a combination of 25% sorghum sugar: 75% granulated sugar had the highest sensory value. Biscuits with 100% palm sugar sweetener which have the best nutritional value are found in biscuits with a combination of 100% palm sugar sweeteners examined from the total sugar content of 26.5% and calories of 4765.0 cal.